Assessment of Cardiovascular Risk in a Patient with Rheumatoid Arthritis - Xamrayev Xamza; Goyibov Salim; Tagaeva Dilnoza (Institute of Medico-legal Publications Pvt Ltd, 2021)
Purpose: to study cardiovascular risk on the mSCORE scale in patients with rheumatoid arthritis (RA).Methods: We examined 140 RA patients aged 35 to 60 years. The diagnosis of rheumatoid arthritis wasmade on the basis of the ACR (1987) and ACR / EULAR (2010) criteria. The mSCOREscale (SCORE /EULAR) was used for early detection and prediction of cardiovascular risk.Results: In patients with RA, hereditary risk factors (RF) for cardiovascular diseases were detectedin 31.4%, abdominal obesity in 35%, arterial hypertension (AH) in 63.6%, hypercholesterolemiahypercholesterolemiain 25.7%, and hypodynamia in 37.9% of patients. Smoking accounted for 10.8% ofpatients in the study, as the majority (82%) of the surveyed were women. At the same time, AH was observed1.5 times, hypercholesterolemia 2.1 times more often in men than in women. According to the results of thestudy on the mSCORE scale, 52 (37.1%) had low risk, 64 (45, 7%), a high risk was in 14 (10%), and a veryhigh risk was in 10 (7.2%) patients.Conclusion: In RA patients, the use of the mSCORE scale enables early diagnosis of cardiovascular riskand timely correction of risk factors.